Sociodemographic and clinical factors associated with fractures in older adults treated in a public hospital in Paraguay in 2024 - Da Silva, Márcia Nayane; Poletti Duarte, Rossana Elizabeth; Garlisi-Torales, Luciana Daniela; Chaparro, Marco A. (Salud Integral y Comunitaria, 2026)
Introduction: Fractures in the elderly constitute a significant public health problem due to their high incidence and impact on morbidity and mortality. Globally, an estimated 178 million fractures occurred in 2019, a number that is increasing due to the aging population. Older adults, especially women, are most susceptible, and most of their fractures are caused by low-energy trauma (falls from standing height). Objective: To identify the factors associated with fractures in older adults treated at a public hospital in Paraguay in 2024. Methodology: A descriptive, cross-sectional observational study. One hundred patients aged ≥60 years with a history of bone fracture, treated at the Trauma Service of a surgical specialty hospital between January and July 2024, were included. Sociodemographic data, comorbidities (hypertension, diabetes), and fracture characteristics (anatomical location, mechanism, type, and treatment) were collected from medical records. Results: The mean age was 76.3±7.9 years (median 77); 78% were female. The average body mass index was ~25 kg/m². Sixty-nine percent had hypertension and 34% had diabetes mellitus. The predominant mechanism was a fall from standing height (84%). The most frequently affected bone was the proximal femur (61%), followed by the distal radius (17%) and the proximal humerus (10%). Ninety-eight percent of the fractures were closed (non-compound), and all received surgical treatment. Discussion: Fragility fractures primarily affected older women with common comorbidities, typically occurring due to low-energy falls and affecting osteoporotic bones (hip, wrist, humerus). These findings are consistent with international literature and highlight the need to prevent falls and implement proactive management of bone health (e.g., treatment of osteoporosis) to reduce the incidence of fractures and their consequences in the elderly population.